Kompetencja fonologiczna w języku obcym z punktu widzenia studentów kierunków filologicznych. Perspektywa przyszłej kariery zawodowej - Korczyński, Oskar (Neofilolog, 2025)
Phonological competence, which is one of the components of linguistic competence, poses many challenges for learners and language teachers. Among these, the neurolinguistic determinants of the learner, the role of teacher feedback and the question of the choice of pedagogical norm are particularly relevant. This results in a multitude of beliefs and diverse representations around phonological competence. The aim of this study was to observe these beliefs and representations in a sample of 60 students from various philology courses. For this purpose, they were asked to complete a questionnaire containing closed and open-ended questions. The results suggest that the students consider a highly developed phonological competence to be important for their future work as philologists, even though they understand the concept in different ways.